2010
DOI: 10.3344/kjp.2010.23.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of High-Sensitivity C-reactive Protein and Erythrocyte Sedimentation Rate in Low Back Pain Patients

Abstract: BackgroundChronic low back pain can be a manifestation of lumbar degenerative disease, herniation of intervertebral discs, arthritis, or lumbar stenosis. When nerve roots are compromised, low back pain, with or without lower extremity involvement, may occur. Local inflammatory processes play an important role in patients with acute lumbosciatic pain. The purpose of this study was to assess the value of erythrocyte sedimentation rate (ESR) and high sensitivity C-reactive protein (hsCRP) measurements in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
0
23
3
Order By: Relevance
“…CRP-an acute phase reactant is an indicator of low grade inflammation. The higher level in our cases denotes the probable role of inflammation in back pain [25].…”
Section: Discussionmentioning
confidence: 50%
“…CRP-an acute phase reactant is an indicator of low grade inflammation. The higher level in our cases denotes the probable role of inflammation in back pain [25].…”
Section: Discussionmentioning
confidence: 50%
“…We considered that the pathophysiology of LSS is complex [2], and although mechanical compression of the nerve root is a major factor, inflammatory effects [19] and some other causes, such as depression and the subjective quality of feeling, also affect both pain intensity and unpleasantness [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, only one study could be found concerning patients with chronic lumbar pain and radicular pain. In another study, CRP and ESR levels were expected to increase dependent on increased inflammatory reactions, but they did not increase (7).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory measurements of acute phase proteins are important indicators for the degree of inflammation and response to treatment. CRP is a sensitive marker of inflammation and tissue damage, but erythrocyte sedimentation rate (ESR) is not a specific marker (7).…”
Section: Introductionmentioning
confidence: 99%